Diagnosis dan Manajemen Obstruksi Jalan Napas Atas (Jackson 1) Akibat Infeksi Difteri pada Wanita Hamil - Dwikarlina, Intan; Wijaya, Rendy; Yulia Rusmayanti, Mega; Antariksa, Genta; Candradikusuma, Didi (RSUD Dr. Saiful Anwar Province of East Java, 2025)
Diphtheria is an infectious disease caused by Corynebacterium diphtheria, which generally causes inflammation of the airways, leading to severe symptoms that can be life-threatening. Indonesia is listed as one of the ten countries with the highest cases of diphtheria worldwide. However, studies on cases of diphtheria infection, especially in the pregnant women population, have rarely been reported. A 28-year-old woman presented with shortness of breath. Complaints accompanied by difficulty swallowing and speaking. The patient had a child who died due to similar symptoms. Signs of airway obstruction are found as inspiratory stridor and suprasternal retraction, pseudomembranes in the pharynx, and subcutaneous crepitation in the colli. Diphtheria infection was confirmed through a throat swab examination with Neisser staining and culture. In addition to isolation, the patients were administered oxygen therapy, anti-diphtheria toxin, penicillin procaine, dexamethasone, and additional supportive therapy. Diphtheria infection is transmitted through direct contact, droplets or contaminated items. Manifestations of laryngeal diphtheria generally come from the extension of tonsillar-pharyngeal diphtheria symptoms, including sore throat, hoarseness, and advanced respiratory obstruction. A definite diagnosis is made by isolating the bacteria or finding an increase in serum antibodies. Therapies targeting infectious conditions and supporting obstetrics help improve the overall patient condition. Diphtheria is a highly contagious and potentially fatal disease, especially for pregnant women; thus, immediate diagnosis is needed. Isolation and appropriate management alleviate upper airway obstruction. Diphtheria management should include both curative therapy and preventive to protect the community further and prevent outbreaks from emerging.